1998
DOI: 10.1002/(sici)1097-4601(1998)30:6<385::aid-kin1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen autoignition at pressures above the second explosion limit (0.6-4.0 MPa)

Abstract: The investigation of high-pressure autoignition of combustible mixtures is of importance in providing both practical information in the design of combustion systems and fundamental measurements to verify and develop chemical kinetic models. The autoignition characteristics of hydrogen-oxygen mixtures at low pressures have been explored extensively, whereas few measurements have been made at high pressures. The present measurements extend the range of pressures up to where few measurements have yet been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 29 publications
(31 reference statements)
2
39
1
Order By: Relevance
“…Only eight elementary reactions have to be considered to accurately describe the low-temperature autoignition regime [5,6,9], and each of them (resp. 1f, 2f, 3f, 4f, 6b, 10f, 11f, 12f) is included in the subset of 12 reactions considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Only eight elementary reactions have to be considered to accurately describe the low-temperature autoignition regime [5,6,9], and each of them (resp. 1f, 2f, 3f, 4f, 6b, 10f, 11f, 12f) is included in the subset of 12 reactions considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Hochgreb at the Massachusetts Institute of Technology (MIT) used an air driven, oil damped RCF piston system [20] to study hydrogen auto-ignition [21]. Lee and Hochgreb have performed detailed modeling of the suppression of vortices, which are formed by the piston in this facility during compression, and the heat transfer that occurs within the MIT RCF [22].…”
Section: Introductionmentioning
confidence: 99%
“…The design for these creviced piston heads was originally devised at MIT [20,21,22], who found that the temperature field obtained using creviced pistons is almost homogeneous compared to that obtained using flat piston heads which is predicted to lead to far greater gas in-homogeneities in the post-compressed combustion chamber. A computational fluid dynamics (CFD) study carried out at NUI Galway [23] supports this view.…”
Section: Rapid Compression Machinementioning
confidence: 99%